Enzymatic synthesis of kojic acid esters and analysis of depigmenting activities using in vitro and in vivo models - Lajis, Ahmad Firdaus (2016)
Kojic acid (KA) is a commonly known skin-whitening agent in cosmetic products. However, KA is not oil soluble that makes it difficult to be incorporated in cosmetic formulation. Therefore, KA esters are synthesized to increase its lipophilicity that allows it to be easily incorporated into cosmetic products. In previous study, kojic acid esters were synthesized via chemical processes using chemical catalysts. Chemical catalysts are not environmentally friendly and caused more harm to consumers compared to biocatalyst. The handling process and removal of hazardous chemical from products may also increase cost of production. In this study, the enzymatic synthesis of KA esters was proposed and performed in various types of bioreactor such as stirred tank reactor (STR), packed bed reactor (PBR) and fluidized reactor (FR) using three commercial immobilized lipases (TLIM, RMIM and N435) where the performances were compared. The alternative approaches and methods (solvent and solvent-free systems) for the synthesis of KA esters in different reactor systems were also investigated. Various enzymatic and bioreactor operation parameters were manipulated aimed at solving various problems in enzymatic reactor operation such as shear effects due to stirring and potential of lipase reusability. The physical, chemical and depigmenting properties of KA esters were also studied. The depigmenting activity of KA esters was evaluated using in vitro and in vivo models using B16F1 and zebrafish mbryo,respectively.For esterification using N435 lipase, very high yield (up to 50%) of KA esters were synthesized in STR compared to PBR and FR. The enzymatic esterification of KA esters in STR would currently be the best alternative as compared to other types of reactor tested, despite some of its weaknesses. Solvent-free system can be another alternative but the handling of saturated fatty acid in liquid form can be difficult because high temperature is required. Under ultraviolet (UV) light, skin color turn dark due to an increase of alpha-melanocyte stimulating hormone (α-MSH) and oxidation process. Kojic acid monopalmitate (KAMP) showed slightly higher inhibition to melanin formation compared to KA, kojic acid monooleate (KAMO) and kojic acid monolaurate (KAML), as analysed by in vitro model using α-MSH stimulated B16F1 cells. The reduction of melanin formation was correlated to the reduction of mushroom tyrosinase and cellular tyrosinase activity in B16F1. KAMP also showed greater antioxidant activity than KA, KAML and KAMO as measured in anti-lipid peroxidation method and other antioxidant assay.Evaluation of the depigmenting activity of KA esters by in vivo model using zebrafish embryo indicated that KAMP has better depigmenting activity than KA and KAMO. The toxicity level of KA and KA esters were also estimated where KAMP gave lower toxic effect compared to KA, KAML and KAMO, as evaluated using B16F1 cells, G361 cells and zebrafish embryo. Zebrafish embryo treated with KAMP also showed higher survival rate, high hatchability, stable heart-beat rate and no significant teratogenic effect as compared to KAML.The results from this study have demonstrated that KA esters can be synthesized in solvent-free system as an alternative to solvent system. Solvent-free system has advantage of using chemical at low cost and environmental friendly process. Large scale production of KA esters could be performed using STR and FR, where the yield could be further improved by the improvement of mixing condition and optimization of the process variables. The absence of toxic and better depigmenting effect of KA esters as compared to KA suggest that KA esters are safe to be applied as skin-whitening agents in commercial cosmetic formulation.